Innovative Method of Carrying Out Coastal Protection Works: Monitoring Coastal Risks and Soft Solutions in Benin - Hountondji, Babilas; Ayitchéhou, Lambert K.; de Paule Codo, François; Aina, Martin P. (European Journal of Applied Sciences, 2025)
Coastal erosion is a phenomenon of natural or anthropogenic origin that affects many coastal regions around the world. In response to its worsening over time, adaptation strategies have been developed: construction of dikes, operations to re-silt beaches, rock structures, etc. Among these strategies, the establishment of sand dunes is a territorial entity which fluctuates in space and time depending on natural (tide, erosion, sedimentation, etc.) and human factors (dams, etc.). The Beninese dune cord in the sector of the mouth of the Mono River in the commune of Grand Popo is in a state of lamentable degradation: due to anthropogenic pressure, mainly through urbanization, tourism, illegal sand extraction and even all the agricultural activities practiced in the area, something which has favored wind erosion and the invasion of the Mono River by sand. Faced with this alarming situation, the French Fund for the Global Environment (FFEM) initiated a project “Soft solutions and monitoring of coastal risks in Benin” with a view to restoring the dune system in the sector of the mouth of the Mono River in the commune of Grand Popo to safeguard the ecological and ecosystem role of this area. The objective of this work is to consolidate and sustain the advances in coastal observation mechanisms, at the regional and national levels, to influence public policies on the issues of coastal risks and the management of coastal areas but also to initiate a series of field, pilot activities for the implementation of soft solutions for coastal protection. The results obtained concerning the installation of typhavelles and Epis Maltais Savard (SEMS) for fixing mobile dunes at the Grand Popo wetland are very encouraging for the preservation of this site of international importance.